Response and rehabilitation of historic monuments after the gorkha earthquake - Weise, Kai (2019)
A 7.8 magnitude earthquake struck Nepal on April 25, 2015, followed by numerous aftershocks, devastating hundreds of villages, residential buildings, and historical monuments. The destruction was extensive and the response in respect to cultural heritage needed to be coordinated. This chapter provides an overview of the response to the destruction to Nepal’s cultural heritage and the challenges of rehabilitation. During the past years, the Kathmandu Valley World Heritage Site has been preparing for the earthquake that was to strike Nepal. Clearly, one is never fully prepared. After the initial response phase and with the onslaught of the monsoon rains, rehabilitation planning began. Rehabilitation however cannot focus just on rebuilding the monuments. The tangible is an expression that has over the centuries always been damaged and rebuilt. Sustainability is achieved when the community ensures continuity and the concept of continuity of culture become the basis for reconstruction.